Seeds of Resistance, Seeds of Hope : Place and Agency in the Conservation of Biodiversity - Andrews-Swann, Jenna, 1980-; Rhoades, Robert E.; Nazarea, Virginia D. (Virginia Dimasuay), 1954- (Book collections on Project MUSE., 2013)
"Without denying the gravity of the problems of feeding the earth's population while conserving its natural resources, Seeds of Resistance, Seeds of Hope reminds us that there are many positive movements and developments, especially at the grass-roots level, that demonstrate the power of opposition and optimism"--